Edith Stein and Regina Jonas : religious visionaries in the time of the death camps - Silverman, Emily Leah; Cambridge eBooks (Durham : Acumen Publishing, 2013)
This ground-breaking book examines the lives of two extraordinary, religious women. Both Edith Stein and Regina Jonas were German Jewish women who demonstrated 'deviant' religious desires as they pursued their spiritual paths to serve their communities during the Holocaust. Both were religious visionaries viewed as iconoclasts in their own times. Stein, the first woman to receive a doctorate in philosophy from Husserl, the founder of phenomenology, claimed her Jewish identity while she was still a cloistered Carmelite nun. Jonas, the first woman rabbi in Jewish history, served as a rabbi in Berlin and Theresienstadt concentration camp. A study of a contemplative and a rabbi, the book ranges across many spiritual and theological questions, not least it offers a remarkable exploration of the theology of spiritual resistance. For Stein, this meant redemption and the transmutation of suffering on the cross; for Jonas, acts of compassion bring the face of God into our presence.
Why Edith Stein? Why Regina Jonas? -- Stein's and Jonas's views of women: the philosophy student and the rabbinical student -- St Teresa Benedicta of the Cross reveals the whole megillah as Edith Stein -- Regina Jonas: from candidate to rabbinerin -- Stein suffering on the cross: the call of Abram Lech Lecha -- Rabbinerin Regina Jonas: seeing the face of the Shekhinah -- A theology of resistance as liberation in the death camps.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Stein, Edith, -- Saint, -- 1891-1942.; Carmelite Nuns -- Germany -- Biography; Jonas, Regina, -- 1902-1944.; Women rabbis -- Germany -- Berlin -- Biography; Women concentration camp inmates -- Biography; Christian converts from Judaism -- Religious life; Jewish women -- Religious life; Gender identity; Electronic books